Organizational preparedness domains and indicators of educational organizations for students with disabilities in pandemic times: A scoping review - Vlachou, Anastasia; Kalaitzi, Stavroula; Tsermidou, Lia; Toulia, Anastasia; Papazoglou, Theodora; Fyssa, Aristea; Papazis, Filippos (Frontiers in Education, 2023)
Abstract Background: The impact of the COVID-19 pandemic on educational systems has caused a profound shift on the organization and delivery of education worldwide. The effects of the pandemic crisis on educational systems proved to be detrimental for students with disabilities highlighting not only the looming social and educational inequalities, but also the huge gap in organizational preparedness for education. Namely, to identify the main areas (domains) of preparedness which will guide the process of organizational preparedness and the sub-themes (indicators) per domain which will help educational organizations to evaluate their level of preparedness, identify potential gaps and set priorities for preparedness planning. Methods: Scoping review with thematic analysis was performed on literature published from 2010 to 2022. Six scientific databases (PsycInfo, Web of Science, Eric, Scopus, Proquest, JSTOR) and one academic search engine (Google Scholar) were examined in order to identify publications (peer-reviewed and preprint) in English. The search strategy and robust eligibility criteria were defined by the authors, who also performed screening of the papers, eligibility decisions and key data extractions. A thematic analysis was applied to define the organizational preparedness domains and indicators per domain, informed by a system thinking approach for educational organizations. Conflicts were collaboratively resolved after each step. All members of the research team were involved in the data synthesis. Results: From 1564 publications identified, 216 were included in the final analysis. Six domains and 14 indicators were identified. Conclusion: The organizational preparedness in educational organizations in pandemic crisis times needs to be prioritized in the educational policy agenda, drawing special attention on students with disabilities. The identified preparedness domains and indicators may guide the policy dialogue and inform accordingly a system thinking change approach in education and disability. Keywords: organizational preparedness, preparedness domains and indicators, educational organizations, pandemic, coronavirus, students with disabilities